Acquisition of IDH2 mutations in relapsed/refractory AML is associated with worse patient outcomes. (30th August 2021) - Song, Amy; Altabbakh, Omar; Sallman, David A.; Padron, Eric; Talati, Chetasi; Hussaini, Mohammad O.
Abstract: Objectives: The presence of targeted therapy, Enasidenib, for IDH2 ‐mutated AML underscores the importance of understanding the clonal dynamics of IDH2 mutations, which has not been elucidated. In the largest study of IDH2 clonal dynamics, we detail the IDH2 ‐evolutionary patterns and their clinical significance. Methods: We analyzed ~6000 patients with NGS results to identify 120 AML patients with IDH2 mutations and longitudinal NGS testing. IDH2 mutation status was recorded at diagnosis, remission, relapse, and persistent disease. Results: One hundred and five patients were IDH2 ‐positive at the initial diagnosis, and 15 acquired the mutation later. Of those 15 patients, 7 patients gained the mutation during persistent disease, 6 during relapse, and 2 at remission. Twenty‐one patients (18%) who were IDH2 ‐positive in a prior test remained IDH2 ‐positive in remission. Twenty‐four patients with IDH2 ‐positive AML were IDH2 ‐positive at relapse. IDH2 ‐positive at diagnosis had better survival than IDH2 mutation acquired later in disease ( P  = .024). Patients who were IDH2 ‐negative in remission had significantly improved survival ( P  = .002). Also, loss‐of‐ IDH2 mutation with persistent disease had better OS ( P  = .035). Conclusions: There are 70% that clear IDH2 in disease remission. 12% gain IDH2 mutation later, usually in the setting of refractory/relapsed AML. These patients fared worse. Longitudinal IDH2 testing may be helpful in prognostic stratification.